Channel estimation for OFDM systems with transmitter diversity in mobile wireless channels. - Ye Li (IEEE Journal on selected areas in communications)
Transmitter diversity is an effective technique to improve wireless communication performance. In this paper, we investigate transmitter diversity using space-time coding for orthogonal frequency division multiplexing (OFDM) systems in high-speed wireless data applications. We develop channel parameter estimation approaches, which are crucial for the decoding of the space-time codes, and we derive the MSE bounds of the estimators. The overall receiver performance using such a transmitter diversity scheme is demonstrated by extensive computer simulations. For an OFDM system with two transmitter antennas and two receiver antennas with transmission efficiency as high as 1.475 bits/s/Hz, the required signal-to-noise ratio is only about 7 dB for a 1% bit error rate and 9 dB for a 10% word error rate assuming channels with two-ray, typical urban, and hilly terrain delay profiles, and a 40-Hz Doppler frequency. In summary, with the proposed channel estimator, combining OPDM with transmitter diversity using space-time coding is a promising technique for highly efficient data transmission over mobile wireless channels